Perceived Impact Of Environmental Factors On Teaching And Learning Of Physical Education In Rivers State - Deemua, G. A. (Advances in Social Sciences Research Journal, 2019)
This paper examines perceived effects of environmental factors on teaching and learning of physical education and sports in Rivers State. Some of the identified environmental factors negatively affecting teaching and learning of physical education and sports include students’ health, school location, socio-cultural beliefs, instructional facilities and community/family background. It is therefore recommended amongst others that the government and stakeholders in education should make the school environment attractive and stimulating and employ good instructional strategies to enhance students’ interest, attitudes and achievements in teaching and learning physical education and sports.